Two-step chemical bath deposition enhanced mobility of PbS thin films. (December 2021) - Chalapathi, U.; Park, Si-Hyun; Choi, Won Jun
Abstract: A two-step chemical bath deposition (CBD) method that involves the deposition of films at two different bath temperatures is developed to enhance the grain growth and hole mobility of lead sulfide (PbS) thin films. The films deposited at three different conditions; first at 60 °C for 2 h, second at 30 °C for 1 h and at 60 °C for the subsequent 1 h, and finally at 60 °C for 1 h and at 30 °C for the subsequent hour. The deposition of PbS at only 60 °C for 2 h leads to the formation of cubic crystals with different sizes and hole mobility of 43.8 cm 2 V −1 s −1 . The deposition at a low temperature of 30 °C for the initial 1 h followed by the deposition at a high temperature of 60 °C for the subsequent hour increases the grain size and hole mobility to 62.2 cm 2 V −1 s −1 . However, the deposition of PbS at a high temperature of 60 °C for 1 h followed by the deposition at a low temperature of 30 °C for the subsequent hour decreases the grain size and hole mobility to 32.1 cm 2 V −1 s −1 . The PbS film deposited at low temperature in the first step acts as a seed layer for the growth of large-grained PbS in the second step. Thus, the two-step CBD method enhances the grain growth and hole mobility of PbS films. Hence, the two-step CBD method is very much useful for the growth of PbS for its applications in optoelectronic devices. Highlights: PbS thin films prepared by a two-step chemical bath deposition. Crystallinity and grain size of PbS increased with the two-step CBD method. Hole mobility of 62.2 cm 2 V -1 s -1 is obtained for PbS deposited by two-step CBD.